Determinants and Consequences of the Severity of Executive Compensation Clawbacks* - Asante‐Appiah, Bright; Sharma, Divesh S. (Contemporary Accounting Research, 2022)
ABSTRACT We examine the determinants and consequences of the severity of executive compensation clawbacks. As one of the most substantial, prolonged, and controversial proposals to reform executive compensation, clawback rules recently regained the SEC's focus. We construct an intuitive clawback severity score and find that clawbacks are considerably heterogeneous and not homogenous as assumed in the literature. Our determinants analyses suggest that clawback severity is increasing in firms with greater board effectiveness and with higher cash and stock awards in director compensation. In contrast, higher director stock option compensation and more powerful CEOs attenuate the severity of clawbacks. The consequences analyses indicate that while severe clawbacks deter financial restatements, management circumvents severe clawbacks by reducing R&D expenses to avoid earnings decreases. One consistent finding throughout our analyses is that the associations are entirely driven by more severe clawbacks. However, we observe that the financial reporting benefits of severe clawbacks can be diminished by the dynamics in the boardroom. Our study extends extant clawback literature, makes a timely contribution to the SEC's decision to reinitiate discussion on clawbacks, and informs various stakeholders interested in the efficacy of clawbacks. Finally, our clawback score can be used to evaluate clawback policies.